Sustainable finance market practices - Adrienne Coleton; Maria Font Brucart; Pilar Gutierrez; Fabien Le Tennier; Christian Moor (European Banking Authority (EBA), 2020)
This paper aims to assess the understanding of environmental, social and governance (ESG) considerations within the banking context and examines the current market practices in this area. To that extent this paper sets out the various definitions of ESG factors and also sets out how these then are converted into and treated as ESG risks. This paper relies upon the lessons learnt from a survey developed by the EBA to gain insights into current market practices with regard to credit institutions' approach to incorporating ESG considerations into their frameworks. The survey especially aimed to collect information from credit institutions on current practices in the following areas: definitions of ESG factors; incorporation of sustainability into business strategies; governance, policies and risk management applicable to ESG risks; ESG and climate-related disclosures; and green financial products.
Keywords: 330; ESG; ESG risks; sustainable finance